Framework for Spatial-Temporal Cross-Functional Planning of Projects by Highway Agencies - France-Mensah, Jojo; Kothari, Chirag; O'Brien, William J.; Khwaja, Nabeel; Gonzalez, Ricardo (Frontiers in Built Environment, 2019)
State highway agencies (SHAs) are tasked with providing short- to long-term plans for developing and maintaining transportation infrastructure. In line with this task, often multiple functional groups in SHAs are responsible for allocating funds from multiple categories to a range of infrastructure assets on the same network—a situation that demands highly effective platforms for collaboration. However, the use of heterogeneous information systems challenges efforts to perform a spatial-temporal analysis of candidate projects proposed by these functional groups. To address this challenge, this paper proposes an integrated framework to improve the collaborative planning of highway projects by SHAs. The major steps in the framework include budgeting, identifying and integrating candidate projects, performing a spatial conflict analysis, classifying conflicts, and developing a response action. These steps are repeated iteratively until there are no unplanned spatial conflicts in the final program or scenario. The proposed framework was implemented by developing a tool in a spreadsheet environment via Visual Basic programming. The developed tool was first validated via a Charrette test involving ten participants with a total of close to forty years of project management experience in cross-functional organizations. The second phase of validation involved feedback from six agency experts after case demonstration involving 340 highway projects. This study contributes to the body of knowledge by providing an integrated platform for different functional groups in SHAs to collaborate more effectively.